2012
DOI: 10.4039/tce.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

Bee (Hymenoptera: Apoidea) diversity within apple orchards and old fields in the Annapolis Valley, Nova Scotia, Canada

Abstract: Bees are important within terrestrial ecosystems, providing pollination, which facilitates plant reproduction. Agricultural regions are large landscapes containing varying proportions of cropland, natural, and semi-natural habitats. Most bees are not restricted to any of these and move freely throughout, exploiting food and nesting resources in favourable locations. Many factors affect bee diversity, and knowledge of these is crucial for promoting healthy bee communities. The main objectives of this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 71 publications
4
70
0
Order By: Relevance
“…Our results are in agreement with earlier surveys in apple orchards of North America, which documented great diversity of bees (Sheffield et al 2003;Sheffield et al 2008;Sheffield et al 2012) and of wasps (Sheffield et al 2008;Mates et al 2012). Abundance and diversity of native bees in agricultural systems are positively correlated with proximity and extent of the surrounding habitat (Steffan-Dewenter 2003; Kremen et al 2004;Taki et al 2007;Sobek et al 2009;Hagen & Kraemer 2010).…”
Section: Identification Of Megachilid Species (Hymenoptera: Megachilisupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with earlier surveys in apple orchards of North America, which documented great diversity of bees (Sheffield et al 2003;Sheffield et al 2008;Sheffield et al 2012) and of wasps (Sheffield et al 2008;Mates et al 2012). Abundance and diversity of native bees in agricultural systems are positively correlated with proximity and extent of the surrounding habitat (Steffan-Dewenter 2003; Kremen et al 2004;Taki et al 2007;Sobek et al 2009;Hagen & Kraemer 2010).…”
Section: Identification Of Megachilid Species (Hymenoptera: Megachilisupporting
confidence: 93%
“…Plants benefit by being pollinated, which assures seed formation and sexual reproduction; and in return, the plant provides the pollinator with nectar, pollen and sweet fruits. Pollination has contributed to the evolution of floral diversity, mainly of angiosperms (Cane 2008;Sheffield et al 2012). Thirty five percent of the world's food production (vegetables, fruits, edible oil crops, stimulants, nuts and spices) depends on crop pollination by honey bees, bumblebees and solitary bees (Kraemer & Favi 2005;Klein et al 2007;Gallai et al 2009;Das et al 2011).…”
Section: Identification Of Megachilid Species (Hymenoptera: Megachilimentioning
confidence: 99%
“…These bee species, especially solitary bees, commonly live within natural, or semi-natural vegetation. Cavity-nesting bees have been shown to respond negatively to intense agriculture, presumably in response to loss of nesting habitat availability (Sheffield et al, 2013). The area bees forage is dependent on their nesting site as central-placed foragers.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, bee species richness was similar for both crops – apple and blueberry ( n = 53 and 51) – and numbers are comparable to other studies investigating wild bees in apple orchards (Russo et al ., ; Blitzer et al ., ) and low‐bush blueberry fields ( Vaccinium angustifolium ) in Maine (Bushmann & Drummond, ), although it was higher than in cranberry fields ( Vaccinium macrocarpon ) in Massachusetts (MacKenzie & Eickwort, ). Here, species diversity in apple, calculated as Simpson's invert (1/D), was similar to apple orchards in Nova Scotia, Canada (Sheffield et al ., ). We found that the blueberry associated bee fauna was more diverse than the apple associated.…”
Section: Discussionmentioning
confidence: 97%